2022
DOI: 10.3390/antiox11101951
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Protects the Ducks from Oxidative Stress Induced by Escherichia coli: Efficacy and Molecular Mechanism

Abstract: Bacillus. subtilis has been widely used in animal husbandry as a potential alternative to antibiotics due to its excellent bacteriostasis and antioxidant activity. This study aims to investigate the effects of Bacillus. subtilis on the protection of ducks from Escherichia coli infection and its mechanism. The four experimental groups include the negative control group, positive control group, antibiotic group and Bacillus. subtilis group. Ducks in positive, antibiotic and Bacillus. subtilis groups are orally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Recent years have highlighted their benefits in aquaculture, notably in enhancing growth performance, disease control, immune response improvement, and digestive enzyme activity [16,17]. Among these, Bacillus species are widely employed as probiotics in aquatic animals [18][19][20][21]. Studies have demonstrated that probiotics do not lead to drug resistance in aquatic species, making them viable antibiotic substitutes [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have highlighted their benefits in aquaculture, notably in enhancing growth performance, disease control, immune response improvement, and digestive enzyme activity [16,17]. Among these, Bacillus species are widely employed as probiotics in aquatic animals [18][19][20][21]. Studies have demonstrated that probiotics do not lead to drug resistance in aquatic species, making them viable antibiotic substitutes [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It secretes exogenous digestive enzymes (Abd El-Moneim and Sabic, 2019), which can improve nutrient digestion. Also, it can improve health, performance, ration efficiency, and it can ameliorate the intestinal morphology of ducks (Guo et al, 2016;Zurmiati et al, 2017b;Li et al, 2022;Sun et al, 2022). However, to date there have been no reports concerning the response of male Bayang duck supplemented with a probiotic Bacillus subtilis FNCC 0059.…”
Section: Introductionmentioning
confidence: 99%